Behaviour of circular concrete filled double skin tubes subjected to local bearing force. (August 2015) - Hou, Chao; Han, Lin-Hai; Zhao, Xiao-Ling
Abstract: This paper presents the behaviour of circular concrete filled double skin tubes (CFDST) subjected to local bearing forces. This is an extension of a previous work on concrete filled steel tubes (CFST). A series of tests were conducted where some key parameters were varied, including loading angle, hollow ratio, chord wall thickness, as well as brace to chord diameter ratio. A finite element analysis (FEA) modelling was established and verified by the test data. Comparative analysis was conducted between the full-range behaviour of CFDST and CFST under local bearing. It was found that the performance of CFDST is considerably affected by the interaction of the outer tube, inner tube and the sandwiched concrete, whilst its bearing capacity depends on the hollow ratio. Finally, based on the load-transfer mechanism analysis, simplified formulae for predicting the strength of CFDST under local bearing forces are presented. Reasonable agreement between the predicted and measured values is achieved. Highlights: Experimental investigation of circular CFDST members under local bearing force. Analytical behaviour of circular CFDST members under local bearing force. Design recommendation for circular CFDST members under local bearing force.